2019
DOI: 10.1111/bre.12400
|View full text |Cite
|
Sign up to set email alerts
|

Clinoform growth and sediment flux into late Cenozoic Qiongdongnan shelf margin, South China Sea

Abstract: The South China Sea continental margin in the Qiongdongnan Basin (QDNB) area has incrementally prograded since 10.5 Ma generating a margin sediment prism more than 4km‐thick and 150–200 km wide above the well‐dated T40 stratigraphic surface. Core and well log data, as well as clinoform morphology and growth patterns along 28 2D seismic reflection lines, illustrate the evolving architecture and margin morphology; through five main seismic‐stratigraphic surfaces (T40, T30, T27, T20 and T0) frame 15 clinothems in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 91 publications
(229 reference statements)
0
19
0
Order By: Relevance
“…Because the fluvial-deltaic system is dominant in the PRMB during the rifting stage (Wu et al, 2016), the relative height is determined by the thickness of the clinoform (Chen et al, 2019; and the rifting rate, as shown in Equation 1. Then, based on the fluvial-deltaic model (Hampson et al, 2014), the sediment migration distance is u(x).…”
Section: Methodsmentioning
confidence: 99%
“…Because the fluvial-deltaic system is dominant in the PRMB during the rifting stage (Wu et al, 2016), the relative height is determined by the thickness of the clinoform (Chen et al, 2019; and the rifting rate, as shown in Equation 1. Then, based on the fluvial-deltaic model (Hampson et al, 2014), the sediment migration distance is u(x).…”
Section: Methodsmentioning
confidence: 99%
“…Amorosi et al, 2019;Plink-Bjorklund, 2019) to shelf-edge scale (e.g. Bryn et al, 2019;Gamberi et al, 2019;Gan, Steel, Olariu, & Almeida Jr, 2019;Olariu et al, 2019;Patruno et al, 2019;Steel et al, 2019) and continental-margin scale (Chen, Steel, Wang, Zhao, & Olariu, 2019;Midtkandal et al, 2019). Continuous and repeated erosion is commonplace in the topset areas, F I G U R E 3 Conceptual section of nested clinoforms as the result of incremental margin growth: as in Matryoshka dolls, progressively smaller-scale clinoforms and clinothems 'appear' as we gradually zoom into a continental margin succession.…”
Section: Clinoform As Sedimentary Archivesmentioning
confidence: 99%
“…The study highlights challenges associated with exploration for sandstone reservoirs in seismic wedges in an outer shelf setting. Chen et al, 2019, integrate sediment cores, well-log and 2D seismic data to analyse a >4-km-thick continental-margin sediment wedge of stacked transgressive-regressive successions, and to estimate the sediment discharge into the Late Cenozoic Qiongdongnan Basin, South China Sea. Their contribution quantifies the along-strike, strongly decreasing sediment flux on clinothems, on both flanks of the supply fairway (likely Red River supply), during the building of the accreting margin.…”
Section: Contributions Of the Special Issuementioning
confidence: 99%
See 2 more Smart Citations